EVALUASI KINERJA DAN PRODUKTIVITAS BWE 203 DAN BELT CONVEYOR PADA PENGGALIAN DAN PENGANGKUTAN BATUBARA DALAM UPAYA MENCAPAI TARGET PRODUKSI PIT MUARA TIGA BESAR UTARA (MTBU) DI PT. BUKIT ASAM, TBK UNIT PERTAMBANGAN TANJUNG ENIM (UPTE) KABUPATEN MUARA ENIM PROVINSI SUMATERA SELATAN - Ardhi Jafrian; Adree Octova (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. PT Bukit Asam, Tbk. Tanjung Enim Mining Unit is a State Owned Enterprise (BUMN) engaged in the coal mining industry. The mining system applied is an open pit mining system with two mining methods, namely the Shovel and Truck method (coventional mining), and the Bucket Wheel Excavator System (continuous mining) method. The coal production target set by PTBA was 230,872 tons in January. The mechanical tools used are 1 (one) unit of Bucket Wheel Excavator, 1 (one) Belt Wagon unit, 1 (one) unit of Cable Rair Car, 1 (one) Hooper Car unit and 1 (one) Tripper Car unit. With the use of the above tools, the production target produced was not achieved in January. So in this study a solution will be sought so that the coal production target set can be increased and can be fulfilled in January. The factors that can influence the production of loading and transport activities are as follows: fill factor, bucket wheel rotation time, number of spills, time of obstacle and work efficiency. From the observations, the time taken for one round of the bucket wheel is 10.10 seconds so that the value of the spill in 1 minute is 83 times. With work efficiency of 26.85% in January, the achievement of production was 186,500.37. In order for production to be improved, efforts need to be made to improve work efficiency by minimizing the obstacles that occur in the field. So that we get 34.14% work efficiency in January with an achievement of 237,136.78 tons. Keywords: BWE, Productivity, Target